Women and Gender in a Lebanese Village : Generations of Change - Jabbra, Nancy W., (Women and Gender: The Middle East and the Islamic World ;, 2021)
In Women and Gender in a Lebanese Village: Generations of Change , Nancy W. Jabbra addresses change in women's and gender roles in a village in Lebanon's Bekaa valley. Employing ethnographic methods and secondary sources, she explores that change from the post-World War II period to the early twenty-first century. The topics of geography and power, family and kinship, education and work, community solidarity, ritual and symbolism, and consideration of the future comprise the substantive part of her monograph. This work is a much-needed comprehensive treatment of women in a contemporary Arab Christian rural community.